High spatial resolution geochemistry and textural characteristics of 'microtektite' glass spherules in proximal Cretaceous–Paleogene sections: Insights into glass alteration patterns and precursor melt lithologies. (1st March 2015) - Belza, Joke; Goderis, Steven; Smit, Jan; Vanhaecke, Frank; Baert, Kitty; Terryn, Herman; Claeys, Philippe
Abstract: Using laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS), we have conducted spatially resolved trace element analysis on fresh, unaltered microtektite glasses linked to the Cretaceous–Paleogene (K–Pg) boundary Chicxulub crater and on their surrounding alteration phases. This unique approach offers the opportunity to study in situ and at high spatial resolution both the mixing of different target lithologies and the variation of the major and trace element budget during the alteration process. In addition, two-dimensional element distribution maps reveal important geochemical information beyond the capabilities of single spot laser drilling. Glasses from two localities in opposite quadrants from the source crater were studied. At the Beloc locality (Haiti), the glass population is dominated by the presence of yellow high-Ca glass and black andesitic glass formed by admixture of carbonate/dolomite/anhydrite platform lithologies with crystalline basement. These glasses alter according to the well-established hydration–palagonitization model postulated for mafic volcanic glasses. REEs become progressively leached from the glass to below the detection limit for the applied spot size, while immobile Zr, Hf, Nb, and Ta passively accumulate in the process exhibiting both inter-element ratios and absolute concentrations similar to those for the original glass. In contrast, The Arroyo El Mimbral locality (NE Mexico) is characterized by abundant green glass fragments high in Si, Al and alkalis, and low in Mg, Ca, Fe. Low Si black glass is less abundant though similar in composition to the black glass variety at Beloc. The alteration pattern of high-Si, Al green glass at the Mimbral locality is more complex, including numerous competing reaction processes (ion-exchange, hydration, dissolution, and secondary mineral precipitation) generally controlled by the pH and composition of the surrounding fluid. All green, high-Si, Al glasses are hydrated and variably enriched in Sr, Ba, and Cs, indicating preferred adsorption from seawater during hydration. Despite the onset of ion-exchange reactions, which only seem to have affected the alkalis, the trace element composition of the green high-Si, Al glass is still largely representative of the original melt composition. Refining the geochemical signature of (altered) melt lithologies may advance our current understanding of glass stability in the natural environment and provide insight into the origin and emplacement of ejecta material during crater formation.